Does Dangdut Music as Pop Culture Influence User Engagement through Content Marketing? Evidence from Indonesian TikTok Users - Idrus Jamalulel; Anfitri Sihombing (Tecno Scientifica Publishing, 2026)
TikTok has emerged as an important platform for disseminating popular culture through digital content marketing. In Indonesia, dangdut music has regained its cultural significance as a genre that shapes user interactions on the platform. Building on this context, this study aimed to examine the influence of popular culture, represented by dangdut music, on user experience and user engagement on TikTok. The study employed a quantitative survey of 389 Indonesian TikTok users, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed that popular culture had significant positive effects on content marketing, user experience, and user engagement. In addition, content marketing positively influenced both user experience and user engagement, while user experience emerged as a strong predictor of user engagement. Furthermore, content marketing partially mediated the relationships between popular culture and both user experience and user engagement. These findings contributed to the literature on popular culture and content marketing by demonstrating how elements of local popular culture could be effectively integrated into digital platforms to enhance user experience and foster stronger user engagement.